Kajian pengendalian permasalahan disiplin dalam kelas oleh guru berpengalaman dan novis di beberapa buah sekolah menengah di Daerah Kuching, Sarawak dan di Maktab Perguruan Batu Lintang, Kuching - Ahmad Shukri, Bin Sudin. (1998)
This research aims to compare variations in ways in which experts and novices overcome disciplinary problems in classrooms. This comparison is based on three important aspects; generative knowledge, conceptual operations, and heuristic approaches. The subjects for this research are 3 experients teachers with 10 years of experience and 3 invoices trainee teachers who have undergone practicum exposures. Five classroom disciplinary problem are presented to the subject to solve.